PENGARUH PEMBERIAN GIPSUM TERHADAP PERUBAHAN BEBERAPA SIFAT FISIK DAN KIMIA ENTISOLS LEMBAH PALU - Danang Widjajanto, Uswah Hasanah, Mukmin, (AGROTEKBIS, 2016)
This study aimed to determine the changes in physical and chemical characteristics of Lembah Palu Entisols added with gypsum. The research used a completely randomized design with four treatments and six replicates thus there were 24 experimental units.  Four gypsum rates were applied including no gypsum added, gypsum added at 10 t ha-1, 20 t ha-1, and 30 t ha-1.  The effect of gypsum was analysed using the Analysis of Variance and the differences between treatments were determined using Least Significant Difference test.  Experimental variable observed were saturated water content,field capacity water content, bulk density, soil porosity, plasticity index, electrical conductivity, and cation exchangeable capacity (CEC), Ca-exch content.  The addition of gypsum significantly affected all soil variables observed except soil porosity and CEC.